2018
DOI: 10.1177/2374373517750414
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Centered Communication Behaviors That Correlate With Higher Patient Satisfaction Scores

Abstract: Background:With increased emphasis on improving the patient experience, clinicians are being asked to improve their patient-centered communication behaviors to improve patient satisfaction (PS) scores.Local Problem:The relationship between clinician communication behaviors and PS is poorly studied in the emergency department (ED) setting. The purpose of this study was to identify whether specific communication behaviors correlate with higher PS scores in the ED setting.Methods:During a quality improvement proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
0
13
0
2
Order By: Relevance
“…However, other studies suggest a positive effect on patient satisfaction when initiatives target both doctors and patients [52] or when clinicians use positive communication behaviors (e.g. begin with open-ended question) [53].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies suggest a positive effect on patient satisfaction when initiatives target both doctors and patients [52] or when clinicians use positive communication behaviors (e.g. begin with open-ended question) [53].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, discharge procedures were identified as an important opportunity for coordinated communication with the patient (table 3). Others have shown that revisions to the discharge procedures intended to make the process more patient-centred and to highlight follow-up requirements, can significantly improve patient experience and satisfaction with discharge 42 43. In addition, a number of environmental factors highlighted by patients could be remedied with little cost and effort (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…This circumstance is the main objective of a healthcare service [4]. Currently, it is not enough that the physician provides competent medical care [47] since patient-centered communication increases satisfaction [48]. For this reason, although patients remember less than half of the information supplied by their doctors [49], the quality and quantity of information received is essential for decision-making by patients [50].…”
Section: Literature Background and Hypothesesmentioning
confidence: 99%